Comparative analysis of human gut- and blood-derived mononuclear cells: contrasts in function and phenotype - Burke Schinkel, Stephanie C.; Barros, Priscila O.; Berthoud, Tamara; Byrareddy, Siddappa N.; McGuinty, Michaeline; Cameron, D. William; Angel, Jonathan B. (Frontiers in Immunology, 2024)
Alterations in the gut immune system have been implicated in various diseases. The challenge of obtaining gut tissues from healthy individuals, commonly performed via surgical explants, has limited the number of studies describing the phenotype and function of gut-derived immune cells in health. Here, by means of recto-sigmoid colon biopsies obtained during routine care (colon cancer screening in healthy adults), the phenotype and function of immune cells present in the gut were described and compared to those found in blood. The proportion of CD4 + , CD8 + , MAIT, γδ + T, and NK cells were evaluated along with their phenotype, expression of integrins, and ability to produce cytokine in response to stimulation with PMA and ionomycin. T cells in the gut were found to predominantly have a memory phenotype as compared to T cells in blood where a naïve phenotype predominates. Recto-sigmoid mononuclear cells also had higher PD-1 and Ki67 expression. Furthermore, integrin expression and cytokine production varied by cell type and location in blood vs. gut. These findings demonstrate the differences in functionality of these cells when compared to their blood counterparts and validate previous studies on phenotype within gut-derived immune cells in humans (where cells have been obtained through surgical means). This study suggests that recto-sigmoid biopsies collected during colonoscopy can be a reliable yet more accessible sampling method for follow up of alterations of gut-derived immune cells in clinical settings.